(untitled) (Environmental Smoke, 2023)
Wildlife is threatened primarily by habitat loss and trafficking. The Wild Animal Screening Centers emerged in this context for animal rehabilitation victims of anthropic actions. This research aimed at describing temporal, spatial, and taxonomic patterns of primates’ reception and destination by the Wild Animal Screening Center in Belo Horizonte-MG to assist their management process and mitigate the effects of illegal trafficking. From 1992 to 2021, 1,895 primates of ten genera and twenty two species arrived at the Wild Animal Screening and Rehabilitation Center. Callithrix was the most frequent genus (n=1,586). Primates came from 92 cities (Belo Horizonte city concentrated 44.9% of this total) in Minas Gerais as well as from Goiás, Amazonas, Ceará, Bahia, and Rio de Janeiro states. The main way animals were received was by collection (n=1,135), followed by voluntary delivery (n=500) and apprehension (n=210). Death (n=100) and release (n=98) destinations were higher when compared to the animals sent to another captivity (n=26). The highest number of primates received (n=127) at this center was in 2008, while the lowest number of them (n=6) was recorded in 2001. Most primates arrived in good body condition (n=108). Individuals with better body conditions spent less time at the Wild Animal Screening and Rehabilitation Center (X2 = 21.684, p=0.00001956). There was also an association between body condition and schemes of destination (X2 = 37.095, p= 0.0000001722). On the other hand, variables such as body condition, sex, origin, and distance from where they came did not influence on the length of stay of individuals at the Wild Animal Screening and Rehabilitation Center (rho=0.1281706; p= 0.07644). The results reinforce the importance of these Centers for wildlife, including primates. They also point out the importance of several actions on different fronts to reduce the trafficking pressure, such as investments in environmental education and science, creation of new wildlife projects, changes in legislation, and more inspection activities.